The plasma membrane calcium pump: biochemistry, physiology and molecular pathology - Carafoli, Ernesto (Henry Stewart Talks, 2007)
Targets of the signaling function of calcium, Decoding of the calcium message by specific calcium binding proteins, Control of calcium in the cell by calcium transporting proteins in the membranes, Calcium pumps: biochemistry, molecular biology, structure and regulation, Similarities in the regulation mechanisms between the two major pumps, that in the endoplasmic reticulum and that in the plasma membrane, Ambivalence of the calcium signal, Calcium signaling defects and related pathologies, Genetic defects of the plasma membrane calcium pumps in hereditary deafness
Archived at 2021/02/25